Kualitas Pelayanan Jasa dan Kepuasan Keagenan Kapal di Pelabuhan Benete Bay - Ari Barata, Fausta; Harry Velasko, Ignasius; Sonny, Imam; Fachrial, Peppy; Ferdiansyah, Anton (Institut Transportasi dan Logistik Trisakti, 2025)
The main problem in this research is that information regarding the loading and unloading process is not conveyed in detail to service users by the ship agency company and also the lack of relationship building between service users and the ship agency company will have an impact on customer satisfaction. The aim of the research is to find out and analyze the main attributes in the company’s service quality, and service user satisfaction as well as what strategies can be used to improve the service quality performance of the PT Bahari Eka Nusantara Company. The research method used is the Customer Satisfaction Index and the Importance Performance Analysis method with respondents namely PT customers. Bahari Eka Nusantara. The research results show that the customer satisfaction index value is 86.65% which is included in the very satisfied criteria and the service attribute that has the most influence on service user satisfaction is that the company can solve problems smoothly. Trust in customers is in line with customer expectations and if problems occur in the loading and unloading process the company always responds quickly.